THE VISUAL CREATION OF PETRUK CHARACTER USING CASTING TECHNIQUE AS WINDOW DECORATION ELEMENTS - Arif Luqman Al Hafidl; Ari Supriyanto (ARTISTIC : International Journal of Creation and Innovation, 2022)
Petruk is one of the punakawan figures in the puppet show who always entertains the audience. Despite his cute appearance, Petruk's figure has exemplary values and admirable values. In addition, Petruk also has a unique body shape, making it fascinating to use him as an inspiration for the creation of metal cast artwork for window decoration. This decorative artwork was made in 4 (four) steps: exploration, experimentation, incubation, and visualization. Five titles were given to the production of this decorative window artwork: "Petruk Ngilo," "Petruk Duding," "Berharap dan Berserah Diri," "Pemomong," and "Petruk Kanthong Bolong." Each of these window decorations represents a symbolic value for our existence as social beings and God's creatures.